STRATEGI PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN DI SEKOLAH ADIWIYATA MANDIRI - Amirul Mukminin (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2014)
School as one of education unit that be able optimize all of learning environment to construct, to strength, or repair continually the process of educational character, including the character of care about surrounding. SDN Tunjungsekar I Malang and SDN Tulungrejo 4 Batu are some of elementary school in Malang that can achieve the predicate as Adiwiyata Mandiri school that have vision and mission as care and cultured surrounding/environment school. The purposes of this research are to know what strategies that uses to construct the character care about environment and students care environment behavior at both of two schools.The result of this research are; (1) the strategy of constructing care about environment character classified into four are through learning and teaching process, the culture of school, extrakulikuler activities, and reinforcement from parents. (2) the behavior of care about environment in both of school such as threw the rubbish on dustbin, take a like and take a dumb in toilet, daily shift program, care attitude with all plants around the school by take care of it all and unbroken it all, and there is effort to reminded people around them to keep environment clean. Also using water sufficiently by turn off water taps after use it is the kind of save water attitude.